Relationship between Sociodemographic and Psychopathology in Communities in Wanci Village, Wakatobi Regency - I Made Wikrama Resindra; Kenwa, Komang Wiswa Mitra; Lintuuran, Rivo Mario Warouw (Faculty of Medicine, Universitas Airlangga, 2023)
Introductions: Mental disorders are a group of symptoms that co-occur in individuals at a particular time. Symptoms of mental disorders can include physical, biological, psychological, and cognitive symptoms. Mental disorders are considered a silent epidemic in rural areas. This condition is caused by the lack of access to health service centers, especially in the 3T areas (Tertinggal, Terdepan dan Terluar) or fall behind, frontier, and outermost. Wakatobi Regency is one of the regencies in Southeast Sulawesi Province, which has 142 islands and is included in the 3T area. Objective: This study aims to determine the sociodemographic description and its relationship with psychopathology in Wanci Village, Wakatobi Regency residents. Methods: This research is included in the cross-sectional survey using an accidental sampling technique. Respondents amounted to 46 people who have fulfilled the requirements. The research instrument used was the Self Reporting Questionnaire-20 (SRQ-20). Results: A total of 46 samples included in the inclusion criteria found that 22 respondents (47.8%) had SRQ-20 values â‰¥6 or experienced mental-emotional disorders. In bivariate analysis using chi-square tests, significant results were obtained (P<0.05) for age (P=0.029) and spouse (P=0.035). Conclusion: In this study, it was found that there was a statistically significant relationship between age and spouse variables on psychopathology.